Effect of a novel quaternary ammonium silane cavity disinfectant on durability of resin–dentine bond. (May 2017) - Daood, Umer; Yiu, Cynthia; Burrow, Michael F.; Niu, Li-Na; Tay, F.R.
Abstract: Objective: The present study examined the effect of a quaternary ammonium silane (QAS) cavity disinfectant on the viability of human dental pulp cells, dentine bond durability and nanoleakage of simplified etch-and-rinse adhesives. Methods: Etched dentine surface of third molars were randomly divided into two adhesive groups, Adper™ Single Bond 2 and Prime & Bond® NT™. For each adhesive, the teeth were randomly assigned to five cavity disinfectant groups ( N = 6): Group 1: deionised water (control); Group 2: 2% chlorhexidine (CHX); Group 3: 2% QAS; Group 4: 5% QAS and Group 5: 10% QAS. The cavity disinfectants were applied on etched dentine surfaces for 20 s, followed by adhesive application. The bonded teeth were sectioned for bond strength testing at 24 h, 6 months and 12 months. Viability of human dental pulpal cells was examined using MTT assay. Bond strength data were analysed using 3-way ANOVA and Tukey test. Interfacial nanoleakage was evaluated after 24 h and 12 months and analysed using Kruskal–Wallis test. Results: Significant differences in bond strength were observed for the factors disinfectants ( p < 0.001) and time ( p < 0.001); while the factor, adhesive, was not significantly different ( p = 0.203). The 2% QAS cavity disinfectant preserved bond strength of both adhesives and reduced interfacial nanoleakage after 12 months. Cell viability was the lowest for 2% CHX, followed by 2% QAS and the control. Conclusions: The 2% QAS cavity disinfectant demonstrated greater cell viability compared to 2% CHX, with no adverse effect on immediate bond strength and preserved bond stability over time. Clinical significance: Incorporation of 2% quaternary ammonium silane cavity disinfectant in the resin–dentine bonding protocol enhances the success rate of bonded restorations.